Pertumbuhan Perusahaan Transportasi Laut di Indonesia - Akhmad Eko Handoko; Aswanti Setyawati; Yosi Pahala (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2020)
The purpose of this study is to determine the effect of the corruption perception index and business risk on the growth of sea transport companies listed on Indonesia Stock Exchange period 2013 - 2017. The growth of the open sea transport companies has decreased. Therefore, efforts are needed to increase the company’s growth. The main focus of this research is the effect of the corruption perception index mediated by business risk to the company’s growth. The study was using quantitative method with a path analysis approach. The total samples from secondary data was 65 observations from 13 companies with a 5-year observation period taken by purposive sampling technique. The study shows that there is a positive effect of business risk on the company’s growth, therefore, to increase the company’s growth, the company should increase their business risk.